Does the impact of board independence on large bank risks change after the global financial crisis? - Vallascas, Francesco; Mollah, Sabur; Keasey, Kevin (Journal of Corporate Finance, 2017)
The view that the independent directors of large banks should contribute to safeguarding the interests of bank creditors and taxpayers, by exercising a stringent risk oversight of bank executives, has gained ground in the aftermath of the 2007–2009 crisis. Using a cross-country sample of large banks for the period 2004–2014, we show that post 2009 an increase in board independence leads to more prudent bank risk-taking compared to the rest of the sample period. This effect materializes via independent boards favoring increases in bank capitalization and decreases in bank portfolio risk after the global crisis. Additional analyses demonstrate, however, that these results do not hold for all large banks in our sample but are confined to the group of banks benefiting from a government bailout during the crisis. In most large international banks board independence does not contribute to safeguarding the interests of bank creditors and taxpayers by constraining bank risk-taking.